2003
DOI: 10.1152/japplphysiol.00824.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation-induced oxidative stress in the diaphragm

Abstract: Prolonged mechanical ventilation (MV) results in oxidative damage in the diaphragm; however, it is unclear whether this MV-induced oxidative injury occurs rapidly or develops slowly over time. Furthermore, it is unknown whether both soluble (cytosolic) and insoluble (myofibrillar) proteins are equally susceptible to oxidation during MV. These experiments tested two hypotheses: 1) MV-induced oxidative injury in the diaphragm occurs within the first 6 h after the initiation of MV; and 2) MV is associated with ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
171
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(194 citation statements)
references
References 30 publications
15
171
1
7
Order By: Relevance
“…Heart rate (365 Ϯ 9 beats/min) and mean blood pressure (90 Ϯ 4 mm Hg) homeostasis were maintained during MV across all treatment groups. Blood gas homeostasis and pH (data not shown) were maintained within physiologic levels during the experiment as reported previously (1,4,6,18). Because sepsis is associated with diaphragmatic contractile dysfunction, strict aseptic techniques were followed throughout the experiments (1,4,6,18).…”
Section: H Of MVmentioning
confidence: 79%
See 3 more Smart Citations
“…Heart rate (365 Ϯ 9 beats/min) and mean blood pressure (90 Ϯ 4 mm Hg) homeostasis were maintained during MV across all treatment groups. Blood gas homeostasis and pH (data not shown) were maintained within physiologic levels during the experiment as reported previously (1,4,6,18). Because sepsis is associated with diaphragmatic contractile dysfunction, strict aseptic techniques were followed throughout the experiments (1,4,6,18).…”
Section: H Of MVmentioning
confidence: 79%
“…This notion is supported by the observations that new nuclei are incorporated into locomotor skeletal muscle fibers during growth and that nuclei are lost during atrophy (12,14,16). Although it is known that controlled MV decreases protein synthesis and induces proteolysis and myofiber atrophy across all fiber types (6,17,18), it is unknown whether the myonuclear domain of diaphragm myofibers is altered during the fiber atrophy associated with MV.Regulation of myonuclear loss in skeletal muscle could occur through extrinsic death receptor and intrinsic (sarcoplasmic reticulum and mitochondrial) mediated pathways (19). Caspase (cysteine-dependent, aspartate-directed protease) activation results in protein cleavage and functions in intrinsic and extrinsic pathways of apoptosis.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Studies demonstrated the following alterations in the diaphragm after controlled mechanical ventilation: reduced muscle mass 2,10,11 ; diminished type I, IIa, and IIx/b fiber dimensions 3,12,13 ; myofibrillar damage 4 ; enhanced proteolysis 12 ; increased protein oxidation and lipid peroxidation 14 ; reduced expression of the insulin-like growth factor (IGF-I) 3 ; decreased sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase (SERCA-1a) expression 15 ; increased expression of muscle atrophy factor (MAF-box) 16 ; and a decrease in myonuclear content 17 . All of these factors seem to contribute to the development of VIDD, but the precise contribution of each factor and their apparition kinetics has yet to be defined.…”
Section: Ventilator-induced Diaphragmatic Dysfunction (Vidd)mentioning
confidence: 99%